Plankton dynamics of the open Southern Ocean and surrounding the (Sub)Antarctic islands - Stirnimann, Luca (Department of Oceanography, 2023)
The Southern Ocean is a high-nutrient, low-chlorophyll region where primary productivity is limited mainly by iron and light availability, yet it accounts for ~30-40% of global ocean CO2 absorption annually. Marine plankton play a major role in the Southern Ocean CO2 sink as they fix dissolved atmospheric CO2 into organic carbon biomass, much of which supports the ocean food web and a portion of which sinks into the ocean interior, thereby removing atmospheric CO2 on decadal to centennial timescales (i.e., the biological carbon pump). The importance of plankton diversity and dynamics in modulating carbon production and export remains poorly understood, particularly around the many (Sub)Antarctic islands where physical and biogeochemical variability is high. The major motivation for the work presented in this thesis is an improved understanding of the role of the plankton system in Southern Ocean fertility and carbon export, and relatedly, the response of the plankton to environmental forcing such as changes in nutrient dynamics driven by hydrography and island mass effects. To that end, I investigated plankton community diversity and ecological dynamics in the context of nutrient cycling, primary production, and carbon export potential in the open Southern Ocean and in the vicinity of its many island systems. Specifically, I used carbon and nitrogen stable isotope ratios as a tool to quantify carbon export potential and food web dynamics across all major hydrographic zones and basins of the Southern Ocean. Five main findings emerged. Firstly, I developed insights into the major drivers of spatial and temporal variability in the carbon and nitrogen isotope ratios (δ13C and δ15N) of the Southern Ocean's plankton system using circum-Antarctic carbon and nitrogen isoscapes. Along with the drivers commonly invoked by previous studies, I further determined a relationship between the δ13C and δ15N of suspended particulate matter (SPM) and phytoplankton community composition, with diatoms exerting a particularly strong influence on the δ13C and δ15N of the SPM, which is subsequently transferred to the zooplankton. Secondly, I observed that the (Sub)Antarctic islands tend to increase the δ13C and δ 15N of phytoplankton and zooplankton relative to the open Southern Ocean. This trend can be explained by the input of terrestrially-derived iron and other nutrients (e.g., ammonium and/or urea from birds and seals) into the surface layer, which stimulate diatom growth on nitrate and/or exogenous reduced nitrogen sources that are high in δ15N. Thirdly, I applied a new approach using the δ15N of seawater nitrate and SPM to quantify carbon export potential across the summertime Southern Ocean. I found that carbon export potential is highest near the islands and melting sea ice, driven by the input of limiting nutrients (i.e., iron) and by the dominance of diatoms. Fourthly, I found that the δ15N of SPM is a reliable baseline for trophic analysis of the zooplankton system over a large spatial extent of the Southern Ocean (i.e., circum-Antarctic). Since the collection and analysis of SPM samples for δ15N is relatively straightforward, this result should be welcomed by researchers who use such data to reconstruct trophic flows through plankton food webs, as well as the movements and dietary histories of zooplankton in the Southern Ocean. Finally, my new zooplankton δ13C and δ15N isoscapes reveal that during the summer, the primary zooplankton consumers in the Subantarctic waters of the Southern Ocean occupy a low trophic position akin to herbivores, implying that the Subantarctic food web may act to retain organic carbon within the euphotic zone instead of exporting it to depth. By contrast, the primary consumers in Antarctic waters occupy a higher trophic position that suggests they are omnivores and carnivores, which potentially indicates a shorter food chain and thus a stronger biological pump. The work detailed in this thesis suggests new methodological approaches for studying the Southern Ocean plankton system and offers an improved understanding of plankton dynamics and their relationship(s) with the biogeochemical processes that govern the different zones of the Southern Ocean.